2006
DOI: 10.1158/1078-0432.ccr-05-2473
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Inducible Factor-1α and Hypoxia-Inducible Factor-2α Are Expressed in Kaposi Sarcoma and Modulated by Insulin-like Growth Factor-I

Abstract: Purpose: Neoangiogenesis is essential for tumor development. Hypoxia-inducible factor (HIF), a transcriptional factor composed of two subunits (a and h), plays a key role in this process, activating proangiogenic factors such as vascular endothelial growth factor (VEGF). The HIF a subunits are critically regulated by oxygen and are also modulated by growth factors. Kaposi sarcoma (KS) is a highly vascular tumor that releases large amounts of VEGF and for which we have recently described an essential role for t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
43
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 46 publications
10
43
0
1
Order By: Relevance
“…1D). This finding is consistent with reports that expression of HIF-2α by breast cancer cells was unaffected by PI3K inhibition (21), although in other cell types, HIF-2α was reported to be IGF-inducible (22,23).…”
Section: Igf1r Depletion Inhibits Cc-rcc Cell Survival and Expressionsupporting
confidence: 93%
“…1D). This finding is consistent with reports that expression of HIF-2α by breast cancer cells was unaffected by PI3K inhibition (21), although in other cell types, HIF-2α was reported to be IGF-inducible (22,23).…”
Section: Igf1r Depletion Inhibits Cc-rcc Cell Survival and Expressionsupporting
confidence: 93%
“…The α-subunit is hydroxylated at conserved prolyl and asparaginyl residues and targeted for degradation by the von Hippel-Lindau (VHL) ubiquitin E3 ligase complex under normal oxygen conditions. In response to low levels of oxygen, HIF-1α becomes activated and dimerizes with a constitutively expressed HIF-1β, and the complex binds to cis-acting hypoxia response elements in the promoter of target genes, which eventually regulates many cellular activities involved in oxygen homeostasis [3,4,11,[29][30][31]. Consistent with this, Harvey [7,32] suggested that HIFs may be involved in molecular mechanisms which respond to changes in oxygen status during embryo development by expressing genes of HIF-1α, -2α, and -1β subunits in mouse and bovine blastocysts.…”
Section: Discussionmentioning
confidence: 99%
“…In vascular smooth muscle cells, HIF-1α protein levels are strongly increased under normoxic conditions when cells are stimulated with angiotensin II (Ang II), thrombin, and platelet derived growth factor (PDGF) [10]. Similarly, IGF-I can induce HIF-1α protein synthesis and function in several cell lines under normoxic conditions [3,11]. This occurs independently of oxygen tension, but by regulatory mechanisms that involve mitogen-activated protein kinase and phosphatidylinositol 3-kinase/Akt signaling pathways [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…We wondered whether the tube formation was induced by IGF-I directly or by other genes. Previous studies have demonstrated that IGF-I can enhance the expression of VEGF [5][6][7][8] , which plays a central role in the process of angiogenesis. Our results also showed that IGF-I induced VEGF expression and transcriptional activation (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has demonstrated that IGF-I could significantly increase HIF-1α-mediated VEGF expression [5][6][7][8] . We also found that IGF-I enhanced VEGF protein secretion ( Figure 3A) and mRNA expression ( Figure 3B).…”
Section: Dau Inhibited Igf-i-induced Hif-1α Protein Accumulation In Mmentioning
confidence: 99%